2012
DOI: 10.1007/s10535-012-0029-y
|View full text |Cite
|
Sign up to set email alerts
|

Transformation with a gene for myo-inositol O-methyltransferase enhances the cold tolerance of Arabidopsis thaliana

Abstract: In this study, we report a function of myo-inositol-O-methyltransferase (Imt1) in response to low temperature stress using transgenic Arabidopsis thaliana. Imt1 gene was constructed identical to the Imt1 gene from a halophyte Mesembryanthemum crystallinum. After cold stress, the Imt1 transgenic plants exhibited stronger growth than the wild type plants. The elevated cold tolerance of the Imt1 over-expressing plants was confirmed by the lower electrolyte leakage and accumulation of malondialdehyde, but higher p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The expression profile of Comp3048, which codes for a methyltransferase, maintained high levels during drought stress, especially on D2. It was found that myo-inositol-O-methyltransferase (Imt1) responded to low temperature stress in transgenic Arabidopsis [37] . Trithorax-like H3K4 methyltransferase from barley is drought inducible [38] .…”
Section: Resultsmentioning
confidence: 99%
“…The expression profile of Comp3048, which codes for a methyltransferase, maintained high levels during drought stress, especially on D2. It was found that myo-inositol-O-methyltransferase (Imt1) responded to low temperature stress in transgenic Arabidopsis [37] . Trithorax-like H3K4 methyltransferase from barley is drought inducible [38] .…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, some of these key enzymes have been disrupted in their action for comparison purposes by means of the construction of DNA-tagged knockout, or RNA interference mutants. Some of these key enzymes include aldehyde dehydrogenases [40], [67], [73], [78], [101], [110], Alkenal Oxidoreductase (AOR) [83], aldo-keto-reductase [87], [88], [91] and myo-inositol-O-methyltransferase (Imt1) [106], among others. Although most of these studies have been performed in Arabidopsis thaliana , these assays are being extended to plants of further agronomical interest, as initially performed in groundnut [60] by the creation of transgenic plants co-expressing aldo-keto reductase (AKR1) and protein L-isoaspartyl methyltransferase (PIMT2), or in rice and tobacco plants overexpressing AKR1 [61].…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Recently, Zhu et al [41] used a similar strategy as the one developed by Sheveleva et al [39] to express in A. thaliana, a gene coding IMT1, from Mesembryanthemum crystallinum. The transformed plants showed higher growth compared to the wild control line and increased tolerance to cold stress (4°C).…”
Section: Methylated Ins-derivatives In Plant Cell and The Biotechnolomentioning
confidence: 99%